AB0662 UTILITY OF NAILFOLD CAPILLAROSCOPY FOR THE EARLY DIAGNOSIS OF SYSTEMIC SCLEROSIS SPECTRUM OF DISEASES IN ASIA. (June 2019) - Hong, Cassandra; Low, Andrea
Abstract : Background: The utility of nailfold capillaroscopy (NFC) has largely been evaluated in patients with Raynaud's Phenomenon (RP). However, in equatorial countries, RP occurs in only 79% (1) and 84% (2) of patients in Singapore and Malaysia respectively. In the early stages of Systemic Sclerosis (SSc), patients may develop autoantibodies or puffy fingers before the onset of RP (3). Objectives: There is no data on the utility of NFC in patients with non-RP features suggestive of the scleroderma-spectrum of diseases (SSc, mixed connective tissues disease, dermatomyositis). We aim to compare the utility of NFC for the early diagnosis of the SSc-spectrum of diseases in patients who present with and without RP. Methods: Patients referred to our institution for NFC evaluation from March 2010 – March 2017 were recruited. Patients with confirmed diagnosis of a connective tissue disease were excluded. Eligible patients were divided into 4 groups: (I) RP with or without positive aNA; (II) Undifferentiated non-RP features to suggest SSc-spectrum diseases and negative aNA; (III) Undifferentiated non-RP features to suggest SSc-spectrum diseases and positive aNA > 1/400 and (IV) Positive SSc-associated autoantibodies without features to suggest SSc-spectrum diseases. Images were analysed at 200x magnification using a software analysis program. Patients were noted to have normal, aspecific or SSc pattern on NFC, defined by the presence of > 1 giant capillary, avascular areas or >2 dilated capillaries with areas of hemorrhage. Results: 133 patients were recruited (mean age 55 years, 87% female; 76% Chinese, 7% Malay, 10% indian, 7% other ethnicity). ANA was positive in 74 (82.2%) patients (n=25 anti-centromere, n=3 anti-Scl70). Taking into consideration NFC patterns, the clinical outcomes were normal in 32 patients (35.6%), connective tissue disease (CTD) suspected in 33 patients (36.7%), and definite CTD in 25 patients (27.8%). Diagnostic yield for SSc-spectrum of diseases was highest in Groups I and III (Table 1 ). Conclusion: In patients without RP, NFC was most useful to confirm a diagnosis in those with undifferentiated features to suggest SSc-spectrum of diseases and positive aNA. References: [1] Santosa a, Tan C, Teng G, et al. Lung and gastrointestinal complications are leading causes of death in SCORE, a multi-ethnic Singapore systemic sclerosis cohort. Scand J Rheumatol2016Nov;45(6):499-506. [2] Pagalavan L, ong S. Demography, clinical and laboratory features of systemic sclerosis in a Malaysian rheumatology centre. Med J Malaysia. 2007Jun;62(2):117-21. [3] Englert H, Champion D, Wu J, et al. Antitopoisomerase antibody positivity predates nailfold capillaroscopy abnormalities in scleroderma. Postulated classification of 'prescleroderma'. Intern Med J. 2011Feb;41(2):197-9. Disclosure of interests: None declared